2019
DOI: 10.1002/jor.24249
|View full text |Cite
|
Sign up to set email alerts
|

Association between lay perception of morbidity and appropriateness of specialized health care use in adolescent idiopathic scoliosis

Abstract: In absence of school scoliosis screening programs (SSSP) in Canada, this study examined the relationships between the lay person's perception of morbidity and the appropriateness of referral in orthopedics. A cross‐sectional study was conducted with all children consecutively referred in orthopedics for suspected scoliosis. The 831 participants were classified as Appropriate, Late, or Inappropriate referrals for the orthopedic setting. Perceived morbidity was operationalized by: the scoliosis detection origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…She was known to the 4 establishments, as she worked for 20 years with some of their teams, and especially as the leader of a large survey in southwestern Québec on the pathways of care for scoliosis patients. 4 - 6 …”
Section: Introductionmentioning
confidence: 99%
“…She was known to the 4 establishments, as she worked for 20 years with some of their teams, and especially as the leader of a large survey in southwestern Québec on the pathways of care for scoliosis patients. 4 - 6 …”
Section: Introductionmentioning
confidence: 99%
“…These policy decisions presumably had an impact on the management of patients with progressive scoliosis. Retrospectively studying the referral patterns of suspected cases of AIS in orthopaedic clinics, our team [5,9,10] demonstrated that after discontinuation of school screening programs, 20% of patients were referred "late" to a scoliosis clinic to benefit from appropriate and timely conservative management with a spinal brace. Thomas et al reported that in a US county, the number of referrals to orthopaedic clinics for scoliosis in areas without school screening decreased, as well as the number of spinal brace prescriptions [11].…”
Section: Introductionmentioning
confidence: 99%